Energy Absorption Analysis Of Low Speed Frontal Impact For Bumper Beam Through Finite Element Analysis - Su, Muhammad Nasiruddin (UTeM, 2017)
Bumper beam is a safety feature of a car where it functions to absorb impact energy during collision. It is important to improve the bumper beam design in order to improve vehicle safety. Natural fiber composite has been introduced to replace the use of conventional materials because it has advantages of low density, high specific strength and stiffness. Natural fibers like kenaf and hemp have low cost and low density which can replace the glass fibers. Bertam leaves composite has not been explored before in automotive bumper beam. This thesis provided information on different bumper beam design structures focusing on energy absorption analysis. The aim of the research is to determine the capability of energy absorption for five conceptual cross section designs for low speed impact of three materials namely low carbon steel, bertam leaves fiber reinforced polyester and sheet moulding compound. Explicit dynamic simulation was adopted using Ansys LS Dyna software to simulate the frontal low speed impact of bumper beam according to Economic Commission for Europe Regulation No 42. Five new cross section designs have been proposed. AHPTOPSIS method was used to determine best design through identified product design specification of frontal low speed impact low carbon steel bumper beam. Through the seven elements identified in product design specification using AHP-TOPSIS method, cross section 4 (C4) design of bumper beam was the best with Ci value of 0.564. Four parameters namely cross section, wall thickness, materials and ribs influenced the energy absorption and were taken into account for further study. Closed section bumper was slightly better compared to open section bumper beam in energy absorption. C1 closed section bumper beam was capable of absorbing up to 82.79 % of impact energy. Composite material can reduce the bumper beam weight where the bertam leaves fiber reinforced polyester decreased the weight of bumper beam by 87.04 % and sheet moulding compound decreased the weight of bumper beam by 76.75 % compared to low carbon steel. Both composite material with wall thickness of 1.2 mm does not suitable for consideration in automotive bumper beam as the maximum deflection exceed the limit set 30 mm. For wall thickness, as the wall thickness increased, the maximum deflection of bumper beam decreased as well. Two ribs design was added to the C4 bumper beam namely vertical and horizontal rib. A horizontal rib has the highest energy absorption capability which is improved 26.93 % and deflection of bumper beam improved 2 % to 9 %. This thesis can be used as a guideline to design and selecting the best design automotive bumper beam based on the parameters studied and method selection used to determine the best design.